Technological Changes and Digitalization in Human Resources (HR) Management - Firman Agung Pradana; Lusy Rahmawati; Eny Machsusiyah Zin; Iriani Ismai (PT FORMOSA CENDEKIA GLOBAL, 2023)
The aim of this research is to identify technological changes and digitalization in HR management at Caffe Shops in Bangkalan Regency, specifically at a Caffe called Warkop Fafa. The method used is descriptive qualitative. We use 2 data. Primary and secondary data. Primary data was obtained through direct observation and interviews. Meanwhile, we got secondary data from literature collections. The results of our research show that technological changes and digitalization have a big influence on Warkop Fafa's HR management and customer crowds.